PHP Ajax cookbook : over 60 simple but incredibly effective recipes to Ajaxify PHP websites /: over 60 simple but incredibly effective recipes to Ajaxify PHP websites. (2011) - Anbiah, R. Rajesh Jeba; Bhattarai, Roshan; (Software engineer), Sedliak, Milan
No abstract available